Influences of competition level, gender, player nationality, career stage and playing position on relative age effects - Schorer, J.; Cobley, S.; Büsch, D.; Bräutigam, H.; Baker, J. (Scandinavian Journal of Medicine & Science in Sports, 2009)
Relative age, referring to the chronological age differences between individuals within annually age-grouped cohorts, is regarded as influential to an athlete's development, constraining athletic skill acquisition. While many studies have suggested different mechanisms for this effect, they have typically examined varying sports, precluding an examination of the possible inter-play between factors. Our three studies try to bridge this gap by investigating several moderators for relative age effects (RAEs) in one sport. Handball is a sport with position-specific demands, high cultural relevance and a performance context with established developmental structures and levels of representation for males and females. In Study 1, we investigated the influence of competition level and gender on RAEs before adulthood. In Study 2, elite participation, player nationality and stage of career are considered during adulthood. In Study 3, playing position and laterality (i.e., right vs left handedness) are investigated as moderators. Collectively, the results emphasize the complex inter-play of direct and indirect influences on RAEs in sports, providing evidence toward explaining how RAEs influence the development and maintenance of expertise.